Changes in agricultural public finance policies in Korea since Uruguay Round - 김용택 (KREI, 2004)
Although many special farm programs have been implemented and substantial budgets were allocated to the agricultural sector, farm household income has continued to fall. As more attempts to liberalize the agricultural trade such as rice trade negotiations, FTA, and DDA continues, the fall of farm household incomes will increase at a greater rate. In order to design systematic and integrated plans to keep up with rapid structural changes of Korean agriculture, it is so important to objectively evaluate the achievements of old agricultural policies and investment plans, to draw up a policy agenda for the future of Korea's agricultural sector and to suggest future directions to solve agricultural policy problems.
Keywords: Agricultural public investment; Fiscal budget; Structural change of Korean agriculture; Rural economic crisis; Agricultural policy failure; Performance of agricultural public investment programs; Agricultural public investment; Fiscal budget; Structural change of Korean agriculture; Rural economic crisis; Agricultural policy failure; Performance of agricultural public investment programs